Wordwall as a Digital Assessment Tool: Teachers’ Perspectives in an Indonesian Secondary School - Muhammad Ayyub Herianto Ayyub; Abd Halim; Andi Anto Patak (International Journal of Language, Education, and Literature, 2025)
This study explores English teachers’ perspectives on the use of Wordwall as a digital assessment tool in junior high school English classrooms. Amid the growing integration of educational technology, Wordwall has gained popularity for its interactive and game-based assessment features. While previous studies have examined its instructional functions, limited attention has been given to how teachers perceive its use as a formative or summative assessment instrument, particularly in rural educational contexts. Employing a qualitative descriptive design, the study involved semi-structured interviews with two English teachers from SMPN 1 Tinondo, a rural school in Southeast Sulawesi, Indonesia. Data were analyzed thematically using Braun and Clarke’s framework, focusing on patterns in teacher beliefs, experiences, and evaluative judgments of Wordwall’s functionality. The findings revealed that teachers perceive Wordwall positively due to its ability to enhance student engagement, streamline assessment, and deliver immediate feedback. Teachers also noted its alignment with curriculum standards and its potential to support student-centered evaluation. However, the study also highlighted contextual factors that shape these perceptions, including access to digital infrastructure and prior digital literacy. This research contributes to the growing body of literature on digital assessment by offering insights into teacher agency, perception formation, and the pedagogical relevance of gamified tools. It also emphasizes the importance of contextualizing digital tool adoption within rural educational environments. The findings hold implications for policymakers, teacher training programs, and future research on localized technology integration.